the chroniclers. (Foreign Policy)
The article profiles several individuals who made significant contributions in the daily tribulations of immigrants including Tunisian filmmaker Mohamed Ben Attia, German comedian Jan Böhmermann, and English novelist Nikesh Shukla. Attia's film "Hedi," which features how ordinary people cope with the aftermath of the Arab Spring, was awarded Best Debut at the Berlin Film Festival. Böhmermann's poem was the catalyst for a much-needed debate about freedom of expression in Germany. Shukla co-founded the Jhalak Prize, which honors the best British book by a writer of color.